GLOBAL MARKETING AND ADVERTISING UNDERSTANDING CULTURAL PARADOXES - Widya Paramita (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
A book review on Global Marketing and Advertising to Understand Cultural Paradoxes.